An Investigation Of Teachers' Perceptions Towards The Use Of Information And Communication Technology (ICT) In Physical Education - Akmad Sobarna; Rony Mohamad Rizal; Sumbara Hambali; Henry Asmara; Sony Hasmarita; Supriadi, Idris (Metakognisi, 2025)
This study aimed to measure teachers' perceptions regarding the use of Information and Communication Technology (ICT) in physical education. A descriptive quantitative survey approach was employed, with a population of 20 teachers from nine high schools in Cimahi City. The sampling technique used was total sampling, and a teacher perception questionnaire instrument was used to collect data.The data analysis revealed that teachers' perceptions regarding the use of ICT in physical education were low, with a percentage of 40%. This finding suggests that teachers' perceptions are influenced by a lack of understanding and use of ICT in schools, which can impact teachers' low perceptions regarding the use of ICT.The results of this study have implications for teacher education and professional development programs, highlighting the need for relevant training and support to enhance teachers' confidence and competence in using ICT in physical education. Furthermore, this study contributes to the existing literature on the use of ICT in physical education, emphasizing the importance of addressing teachers' perceptions and needs in order to promote the effective integration of ICT in physical education.